Review of the subgenus Chelonus of the genus Chelonus Panzer (Braconidae: Cheloninae) with description of twenty-one new species from China - Zhou, Jin-Jin; Achterberg, Cornelis Van; Tang, Pu; Chen, Xue-Xin (Zootaxa, 2024)
The subgenus Chelonus Panzer, 1806 of genus Chelonus Panzer, 1806 is revised for China and 73 (of which 31 are illustrated) species are recognized. Twenty-one new species, namely, C. (C.) akinakes sp. nov., C. (C.) ameterion sp. nov., C. (C.) angustivertex sp. nov., C. (C.) apicoretusus sp. nov., C. (C.) argoskeles sp. nov., C. (C.) aspros sp. nov., C. (C.) bouommatus sp. nov., C. (C.) brochus sp. nov., C. (C.) columnatus sp. nov., C. (C.) ferrugineus sp. nov., C. (C.) gilvus sp. nov., C. (C.) glomerosus sp. nov., C. (C.) hadrosetron sp. nov., C. (C.) longipectus sp. nov., C. (C.) notochinensis sp. nov., C. (C.) pedinos sp. nov., C. (C.) perspicillatus sp. nov., C. (C.) tanyaisthema sp. nov., C. (C.) transversus sp. nov., C. (C.) truncatus sp. nov. and C. (C.) wuyiensis sp. nov., are described and illustrated. Nine species are recorded from China for the first time, i.e., C. (C.) breviventris Thomson, 1874, C. (C.) capsa Tobias, 1972, C. (C.) cesa Kocak & Kemal, 2013, C. (C.) dauricus Telenga, 1941, C. (C.) fumarius Tobias, 2000, C. (C.) pannonicus Szépligeti, 1896, C. (C.) praepusillus Tobias, 2000, C. (C.) subseticornis Tobias, 1971 and C. (C.) wullii Kittel, 2016. A key to the Chinese species of the subgenus Chelonus Panzer, 1806 is provided.